The Acceptance Rate Toward COVID-19 Vaccine in Africa: A Systematic Review and Meta-analysis - Addisu Dabi Wake (SAGE Publishing, 2021)
Background: The Coronavirus Disease 2019 (COVID-19) pandemic remains serious public issue. COVID-19 vaccine is a vital strategy to prevent this critical pandemic. However, unwillingness to take this vaccine are key barriers to manage the COVID-19 pandemic. The control of this pandemic will depend principally on the people acceptance of COVID-19 vaccine. Therefore, this systematic review and meta-analysis was intended to determine the acceptance rate toward COVID-19 vaccine in Africa. Methods : African Journals OnLine, PubMed, Cochrane Review, HINARI, EMBASE, Google Scholar, Web of Science, and Scopus were used to retrieve related articles. The Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines were used for this study. Random-effect model, a funnel plot, Egger's test, I 2 statistic, subgroup analysis was done. The study was performed by using a STATA version 11 statistical software. Results : A total of 22 studies with 33,912 study participants were included in this systematic review and meta-analysis. From this finding, the pooled prevalence of acceptance toward COVID-19 vaccine among adults in Africa was 48.93% (95% CI: [39.49, 58.37]). The subgroup analysis revealed that the pooled prevalence of COVID-19 vaccine acceptance among adults in Africa was highest (66.03%, 95% CI [62.84, 69.22]) in Southern Africa, and Lowest (24.28%, 95% CI [3.26, 45.30]) in Northern Africa. Conclusion : This study showed that the estimate of the pooled prevalence of acceptance toward COVID-19 vaccine among adults in Africa was very low. All concerned bodies should be actively involved to improve the acceptance rate of COVID-19 vaccine.